CD56dimCD57−NKG2C+ NK cells retaining proliferative potential are possible precursors of CD57+NKG2C+ memory‐like NK cells. Issue 4 (15th September 2020) - Kobyzeva, Polina A.; Streltsova, Maria A.; Erokhina, Sofya A.; Kanevskiy, Leonid M.; Telford, William G.; Sapozhnikov, Alexander M.; Kovalenko, Elena I.
Abstract: Formation of the adaptive‐like NK cell subset in response to HCMV infection is associated with epigenetic rearrangements, accompanied by multiple changes in the protein expression. This includes a decrease in the expression level of the adapter chain FcεRIγ, NKp30, and NKG2A receptors and an increase in the expression of NKG2C receptor, some KIR family receptors, and co‐stimulating molecule CD2. Besides, adaptive‐like NK cells are characterized by surface expression of CD57, a marker of highly differentiated cells. Here, it is shown that CD57‐negative CD56 dim NKG2C + NK cells may undergo the same changes, as established by the similarity of the phenotypic expression pattern with that of the adaptive‐like CD57 + NKG2C + NK cells. Regardless of their differentiation stage, NKG2C‐positive NK cells had increased HLA‐DR expression indicating an activated state, both ex vivo and after cultivation in stimulating conditions. Additionally, CD57 − NKG2C + NK cells exhibited better proliferative activity compared to CD57 + NKG2C + and NKG2C − NK cells, while retaining high level of natural cytotoxicity. Thus, CD57 − NKG2C + NK cells may represent a less differentiated, but readily expanding stage of the adaptive‐like CD57 + NKG2C + NK cells. Moreover, it is shown that NK cells have certain phenotypic plasticity and may both lose NKG2C expression and acquire it de novo during proliferation, induced by IL‐2 and K562‐mbIL21 feeder cells. Graphical Abstract: CD57 ‐ NKG2C + NK cells represent a less differentiated stage of the adaptive‐like CD57 + NKG2C + NK cells, readily expanding in vitro.